Literature Review: Penerapan Sistem Merit Dalam Proses Rekrutmen dan Seleksi Polri - Maulitya, Tannya Athalla; Novitrisani, Yulinda; Supriyadi, Tugimin (Media Hukum Indonesia (MHI), 2024)
The National Police of the Republic of Indonesia, also known as Polri, is a governmental agency responsible for upholding security, enforcing laws, and safeguarding public order. It plays a crucial role in ensuring domestic security by providing protection and services to the people. The selection process for recruiting police officers is a crucial stage in assessing the calibre of potential candidates. This study use a literature review methodology to gather and evaluate diverse literature sources pertaining to pertinent subjects. The research findings demonstrate the significance of implementing a merit-based system in the recruitment and selection process to acquire highly skilled, promising, and competent National Police non-commissioned officers, irrespective of political affiliation, race, ethnicity, religion, nationality, gender, marital status, age, or disability status. However, the merit system is currently not being implemented properly due to deviations from established rules and other hurdles encountered at each level of the selection process.